Effects of individual and neighborhood socioeconomic status on antiretroviral therapy adherence: The role of adherence self-efficacy. (July 2021) - Jiang, Yanping; Li, Xiaoming; Cho, Hyunsan; Brown, Monique J; Qiao, Shan; Haider, Mohammad R
This study aimed to examine the potential mediation effect of adherence self-efficacy on the associations between individual and neighborhood socioeconomic status and antiretroviral therapy adherence in a sample of 337 people living with HIV in South Carolina, United States. Results showed that there were no direct effects of individual or neighborhood socioeconomic status on antiretroviral therapy adherence, whereas both individual socioeconomic status and neighborhood socioeconomic status were associated with adherence self-efficacy, which in turn were related to antiretroviral therapy adherence. These findings suggest that interventions targeting adherence self-efficacy may improve antiretroviral therapy adherence among people living with HIV with low socioeconomic status or those living in socioeconomically disadvantaged neighborhoods.